Journal of research in interactive marketing, volume 9, issue 2 : impact of digital shopping channels on multi-channel marketing and attribution in the. (Journal of Research in Interactive Marketing: Volume 9, Issue 2., 2015)
The studies in this special issue of ""the impact of digital shopping channels on multi-channel marketing and attribution in the changing retail landscape"" put consumers at the center of marketing and attribution and provide implications how retailers can capitalize on digital shopping channels as competitive advantages. The first paper, ""Is this mobile coupon worth my private information? Customer evaluation of acquisition and transaction utility in a mobile coupon shopping context"", by Hyunjoo Im and Young Ha addresses consumer concerns for privacy in using mobile coupons and attempts to u.